Three-Dimensional Evaluation of Morphological Asymmetry of Maxillofacial Complex in Patients Showing Mandibular Prognathism with Facial Asymmetry - HANADA, KOOJI; YAMAKI, MASAKI; HAYASHI, TAKAFUMI; WAKAMATSU, TAKANORI; SAITO, ISAO (The Japanese Journal of Jaw Deformities, 2007)
The present study was designed to three-dimensionally evaluate the morphological asymmetry of maxillofacial complexes such as the maxilla and the mandible, and the state of the maxillary and mandibular deviation in the craniofacial complex of jaw-deformity patients with facial asymmetry. Based upon the results obtained, we tried to classify the states of asymmetry and/or deviation in the cases showing diverted jaw. The subjects comprised 15 patients (10 males and 5 females; 16 years and 6 months old on average) diagnosed as mandibular prognathism with facial asymmetry. All subjects exhibited more than 4-mm deviation of the mandible from the midline on the frontal cephalogram. Pretreatment CT images were taken as data for precise diagnosis in all subjects. Then, sliced CT data were forwarded to 3D reconstruction software Medical Viewer INTAGE 3.1 in order to form the MPR images. After that, 3D-CT images were constructed using the volume rendering (VR) method. After these images were obtained, the three-dimensional ratio of morphological asymmetry of the maxilla and the mandible was analyzed. The three-dimensional ratio of the maxillary and mandibular deviation was also examined. As a result, various types of asymmetry and/or deviation existed and the cases examined were divided into the following eight types: 1. Symmetrical maxilla without deviation in the craniofacial complex, 2. Almost symmetrical maxilla with deviation in the craniofacial complex, 3. Asymmetrical maxilla without deviation, 4. Asymmetrical maxilla with deviation, 5. Asymmetrical maxilla with deviation but complementary to each other, 6. Symmetrical mandible without deviation, and 7. Asymmetrical mandible with deviation, 8. Asymmetrical mandible with deviation but complementary to each other. The present method for three-dimensional evaluation made it possible to classify the state of asymmetry and/or deviation of the maxilla and the mandible in cases with diverted jaw. This VR method may be helpful in determining a more suitable treatment plan for jaw-deformity patients with deviation.